SOCIAL EDUCATION: BUILDING CHARACTER AND CARING IN THE COMMUNITY - Irwan Satria (Adisam Publisher, 2024)
Social education is an important aspect in shaping individual character and instilling a sense of caring for others in society. This research uses the literature study method to examine this matter. The results reveal that the participatory approach requires students to take an active role in the learning and decision-making process, thus increasing their sense of belonging and responsibility for the surrounding environment. The collaborative approach emphasises the importance of cooperation and interaction between students through group activities that enrich communication and conflict resolution. Reflective approaches encourage students to critically review their own learning experiences, helping to develop self-awareness and personal responsibility. Technological approaches utilise digital devices and platforms to enhance the learning process and enable remote collaboration. Meanwhile, the inquiry approach encourages students to explore important questions through research, thus shaping analytical skills and the ability to investigate. By integrating these various approaches, social education can be more effective in preparing students for future global challenges. Comprehensive and dynamic social education encourages students not only to understand but also to contribute positively to social change in their society. This article asserts that social education integrated with diverse approaches can facilitate the formation of strong character and a high sense of caring, both of which are crucial in creating a just and prosperous society. Therefore, innovative and adaptive approaches need to be continuously developed in the social education curriculum to meet the needs of the times and the challenges of the future.